5-bromo-2-hydroxybenzaldehyde (4-phenyl-1,3-thiazol-2-yl)hydrazone - Sadik, G; Necmi, D; Ibrahim, Y; Alaaddin, C; Dinçer, M (Int Union Crystallography, 2004)
In the title molecule, C16H12BrN3OS, the thiazole ring makes an angle of 44.5 (2)degrees with the phenyl ring and an angle of 7.2 (2)degrees with the 5-bromosalicyaldehyde ring. The molecular structure is influenced by O-H...N and O-H...S intramolecular hydrogen bonds. In the crystal, the molecules pack as centrosymmetric dimers via intermolecular N-H...N hydrogen-bonds.
Keywords: Complexes